Development of an Environmentally Friendly Resist-Removal Process Using Wet Ozone - Hideo Horibe; Yousuke Goto (International Journal of Polymer Science)
We investigated the removal of polymers with various chemical structures and the removal of ion-implanted resists using wet ozone. The removal rates of polymers that have carbon-carbon (C–C) double bonds in the main chain were high. The main chain of these polymers may be decomposed. The removal rates of polymers that have C–C double bonds in the side chain were low. The benzene ring in the side chain changes into carboxylic acid, so their ability to dissolve in water increased. The polymers without C–C double bonds were not removed. Removal of B and P ion-implanted resists became difficult with increasing acceleration energy of ions at implantation. The resist with plastic-deformation hardness that was twice as hard as that of nonimplanted resist should be removed similarly to nonimplanted resist. Using TOF-SIMS, we clarified that the molecule of cresol novolak resin was destroyed and carbonized by ion implantation.